Acinetobacter bereziniae sp. nov. and Acinetobacter guillouiae sp. nov., to accommodate Acinetobacter genomic species 10 and 11, respectively - Němec, Alexandr; Musílek, Martin; Šedo, Ondrej; De Baere, Thierry; Maixnerová, Martina; van der Reijden, Tanny J K; Zdráhal, Zbyněk; Vaneechoutte, Mario; Dijkshoorn, Lenie (International journal of systematic and evolutionary microbiology, 2010)
Acinetobacter genospecies (genomic species) 10 and 11 were described by Bouvet and Grimont in 1986 on the basis of DNA-DNA reassociation studies and comprehensive phenotypic analysis. In the present study, the names Acinetobacter bereziniae sp. nov. and Acinetobacter guillouiae sp. nov., respectively, are proposed for these genomic species based on the congruence of results of polyphasic analysis of 33 strains (16 and 17 strains of genomic species 10 and 11, respectively). All strains were investigated by selective restriction fragment amplification (i.e. AFLP) analysis rpoB sequence analysis, amplified rDNA restriction analysis and tDNA intergenic length polymorphism analysis, and their nutritional and physiological properties were determined. Subsets of the strains were studied by 16S rRNA gene sequence analysis and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS or had been classified previously by DNA-DNA reassociation. Results indicate that A. bereziniae and A. guillouiae represent two phenetically and phylogenetically distinct groups within the genus Acinetobacter. Based on the comparative analysis of housekeeping genes (16S rRNA and rpoB genes), these species together represent a monophyletic branch within the genus. Despite their overall phenotypic similarity, the ability to oxidize d-glucose and to grow at 38 degrees C can be used in the presumptive differentiation of these two species from each other: with the exception of three strains that were positive for only one test, A. bereziniae strains were positive for both tests, whereas A. guillouiae strains were negative in these tests. The strains of A. bereziniae originated mainly from human clinical specimens, whereas A. guillouiae strains were isolated from different environmental sources in addition to human specimens. The type strain of A. bereziniae sp. nov. is LMG 1003(T) (=CIP 70.12(T) =ATCC 17924(T)) and that of A. guillouiae sp. nov. is LMG 988(T) (=CIP 63.46( T) =ATCC 11171(T) =CCUG 2491(T)).
Keywords: zastoupení bazí; druhová specificita; fenotyp; Phenotype; Genotype; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Phylogeny; Wound Infection; infekce v ráně; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; hybridizace nukleových kyselin; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; Species Specificity; Acinetobacter; Acinetobacter Infections; geny rRNA; Genes, rRNA; lidé; Humans; Base Composition; infekce bakteriemi rodu Acinetobacter; spektrometrie hmotnostní - ionizace laserem za účasti matrice; RNA ribozomální 16S; odpadní vody; Bacterial Typing Techniques; genotyp; Molecular Sequence Data; Amplified Fragment Length Polymorphism Analysis; DNA, Ribosomal; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Sewage; Nucleic Acid Hybridization